Perancangan Sistem Informasi Akuntansi Persediaan Barang Dagang (Suku Cadang) dengan Menggunakan Software Microsoft Visual Basic 2005 dan SQL Server 2005 Berbasis Client Server pada CV. Ahass Bintang Firdaus Motor - Panji Pirmansyah; Hery Dwi Yulianto (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2017)
Ahass Bintang Firdaus Motor is located in Raya Soreang Street No.32 Soreang-Bandung. The company manages merchandise transaction registration process as manually. This matter develops all working departement in the company works not properly and effectively toward serving report and information neede. Regarding to the issue, the writer title, â€œDesign Merchandise Inventory (Sparepart) Accounting Information System with software Microsoft Visual Basic 2005 and SQL Server 2005 Base of Client Server on the CV. Ahass Bintang Firdaus Motorâ€. The design of the study using primary and secondary data, the academic type of the study using qualitative and quantitative data,exploratories and descriptive methods of research, data collecting technique wich is field study that contains interview, observation and book study. The developing method with methodology that oriented toward process, data and output. The Interasi structure development system And Accounting Information System Design of the konteks diagram, data flow diagram, entity relationship diagram, and flowchart. so that the data processing of revenue report is expected well computerized.